2011
DOI: 10.3892/ijmm.2011.611
|View full text |Cite
|
Sign up to set email alerts
|

Effects and relationship of ERK1 and ERK2 in interleukin-1β-induced alterations in MMP3, MMP13, type II collagen and aggrecan expression in human chondrocytes

Abstract: Abstract. Interleukin (IL)-1β plays an important role in the pathogenesis of osteoarthritis and catabolic processes in articular cartilage. Growing evidence suggests that ERK1/2 activation is involved in IL-1β-mediated matrix metalloproteinase (MMP) 3, MMP13, type II collagen and aggrecan expression in chondrocytes. To investigate the respective effects and the relationship of ERK1 and ERK2, knockdown of ERK1 and/or ERK2 was performed in human chondrocytes using specific small interfering RNAs (siRNAs), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…Within the signaling pathway, visfatin induces vascular endothelial growth factor, and production of matrix metalloproteinases via MAPK [8,16]. In addition, MUC8 or MUC5B expression is induced in response to a wide variety of stimuli, including nerve activation and inflammatory cytokines, such as IL-1β, IL-6, TNF-α, and prostaglandin E 2 through a process involving p38 or ERK1/2 MAPK activation [11,17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the signaling pathway, visfatin induces vascular endothelial growth factor, and production of matrix metalloproteinases via MAPK [8,16]. In addition, MUC8 or MUC5B expression is induced in response to a wide variety of stimuli, including nerve activation and inflammatory cytokines, such as IL-1β, IL-6, TNF-α, and prostaglandin E 2 through a process involving p38 or ERK1/2 MAPK activation [11,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…ROS induce NF-κB activation by modifying the activity of one or more of the kinase enzymes in the NF-κB activation cascades [5]. Recent studies have reported that visfatin increases expression of inflammatory adhesion molecules through an ROS-dependent NF-κB signaling pathway in vascular endothelial cells [5,7,9,16,20]. Therefore, this study focused on correlation between visfatin-induced MUC8 and MUC5B expression and ROS formation via the NF-κB signaling pathway in human airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , IL-1 leads to the activation of ERK, p38 and JNK and is associated with the up-regulated expression of MMPs in chondrocytes and conversely, ERK1/2 inhibition decreases the release of MMP3 and MMP13 by human chondrocytes stimulated with IL-1β [228]. In addition, IL-1β exhibits inhibitory effects on collagen type II and aggrecan whose synthesis is necessary for cartilage repair.…”
Section: Mitogen-activated Protein Kinase (Mapk) Pathwaymentioning
confidence: 99%
“…In addition, IL-1β exhibits inhibitory effects on collagen type II and aggrecan whose synthesis is necessary for cartilage repair. Thus, IL-1β disrupts the balance between catabolic and anabolic activities, which may result in articular cartilage destruction [228], MMP13 is capable of cleaving type II collagen, whereas MMP3 is active against other components of the extracellular matrix, such as fibronectin and laminin.…”
Section: Mitogen-activated Protein Kinase (Mapk) Pathwaymentioning
confidence: 99%
See 1 more Smart Citation